2022
DOI: 10.3390/cells11030328
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Heterogeneity and the Microbiome of Cutaneous T-Cell Lymphoma

Abstract: Cutaneous T-Cell Lymphomas (CTCL) presents with substantial clinical variability and transcriptional heterogeneity. In the recent years, several studies paved the way to elucidate aetiology and pathogenesis of CTCL using sequencing methods. Several T-cell subtypes were suggested as the source of disease thereby explaining clinical and transcriptional heterogeneity of CTCL entities. Several differentially expressed pathways could explain disease progression. However, exogenous triggers in the skin microenvironm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 129 publications
(273 reference statements)
1
12
0
Order By: Relevance
“…Airborne toxins and potential carcinogenetic substances have been investigated as possible trigger of the disease with no clear correlation [ 10 ]. Infective agent susceptibility such as Staphylococcus aureus is thought to be involved in MF/SS pathogenesis and progression [ 11 ]. Genetic aberration along with cytokinc and inflammatory cell changes have been proposed as a putative candidate [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] sometimes providing contradictory results due to the small sample size or the use of different technique of investigation (immunohistochemistry and/or molecular biology analysis).…”
Section: Introductionmentioning
confidence: 99%
“…Airborne toxins and potential carcinogenetic substances have been investigated as possible trigger of the disease with no clear correlation [ 10 ]. Infective agent susceptibility such as Staphylococcus aureus is thought to be involved in MF/SS pathogenesis and progression [ 11 ]. Genetic aberration along with cytokinc and inflammatory cell changes have been proposed as a putative candidate [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] sometimes providing contradictory results due to the small sample size or the use of different technique of investigation (immunohistochemistry and/or molecular biology analysis).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, recent studies of the mouse model have shown that T-cell receptor engagement is an important factor of malignant transformation in CTCL ( 20 ). Moreover, progression of the disease also appeared to be dependent on microbiota ( 20 , 21 ). In addition, Staphylococcus aureus is known as the most common aetiological factor in infections in patients with CTCL, who are colonized by this bacteria in 44% up to 76% ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Staphylococcus aureus is known as the most common aetiological factor in infections in patients with CTCL, who are colonized by this bacteria in 44% up to 76% ( 22 ). S. aureus superantigens may exacerbate and/or perpetuate the clonal expansion of the lymphoma concomitantly with spreading cutaneous inflammation ( 21 , 23 ). In addition, staphylococcal enterotoxin A isolates have been shown to induce signal transducer and activator 3 (STAT3) activation and expression of IL-17, which pathway has been hypothesized as one of the oncogenic factors in CTCL ( 3 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in CTCL skin and high relative abundance of C. tuberculostearicum in stage IVA1 patients (100). Staphylococcus aureus was shown to contribute to CTCL progression (101).…”
Section: Lymphomasmentioning
confidence: 99%